New homogeneous HDL‐cholesterol assay without the influence of high TG sample using the selective detergent to lipoproteins - Ueda, Yasuki (J Clin Lab Anal, 2003)
Homogeneous HDL‐cholesterol assays have been developed and used widely in routine analysis, but they have been reported to give inaccurate results in patients with hypertriglyceridemia. Recently, a new assay based on a new principle without the influence of triglycerides has also been developed and commercialized. We evaluated the basic performance of this new homogeneous HDL‐cholesterol assay and compared it with the conventional polyethylene glycol/cyclodextrin‐modified enzyme (PEGME) method using high‐triglyceride (TG) samples (TG>8,000 mg/L). For samples showing a discrepancy with the conventional method, other precipitation and ultracentrifugation (UC) methods were also used to confirm the values. This new homogeneous assay is based on the selective solubilizing effect of detergent on the different lipoproteins. First, non‐HDL free cholesterol is consumed by enzyme and is cleared as a colorless reactant. Then. HDL‐cholesterol is selectively solubilized by lipoprotein‐specific detergent and reacted with the enzyme. As a result, the precision of this new homogeneous assay was good (CV<2%) over the wide range, and the measurement range was 0 to 2,000 mg/L. This method correlated well with the PEGME method, which is a conventional method for normolipidemic samples (y=0.97x‐3.1, r=0.994, n=424). It also correlated well with the UC method (y=0.99x+0.3, r=0.989, n=53). Fourteen high‐TG samples showed different results from those obtained by the PEGME method. Among these samples, one contained abnormal lipoproteins (probably due to the influence of drug therapy) and gave a significantly different result from that obtained by the PEGME method. However, the values obtained by other methods (precipitation and ultracentrifugation) agreed well with those obtained by this new method. In conclusion, this method shows a good basic performance and is useful for high‐TG samples without any interference. Therefore, it is considered to be very practical for a routine test. J. Clin. Lab. Anal. 17:201–208, 2003. © 2003 Wiley‐Liss, Inc.